The effect of clock drifts on the performance of distributed timestamp ordering - Christos Bouras; Paul Spirakis (3rd COMAD 91, Bombay, India, 1991)
Timestamp–based algorithms have been proposed to protect distributed database from inconsistencies during concurrent access. In such algorithms, transactions may reach a paricular site out of the order of their timestamps, due to unexpected network delays. This causes conflicts which the distributed concurrency control mechanism has to cope with. In this paper we analyze the essential features of the conflict phenomenon under the realistic assumption of the local site clocks out of total synchrony. We quantify the way in which local clock inaccuracies affect the phenomenon of transaction conflicts. In particular, we express the probability of order–reverse as a particular increasing function of the maximum clock drift.